What Does Matter? Liquidity or Profitability: A Case of Sugar Industry in Pakistan - Safdar, Muhammad Zulqarnain; Awan, Muhammad Zahid; Ahmed, Zeeshan; Qureshi, Muhammad Imran; Hasnain, Tafakhar (International Journal of Economics and Financial Issues, 2016)
Keeping in mind the Keynes of the Pakistan's Sugar Industry in its overall economic well-being, the current work objects to examine the liquidity-profitability trade off in Sugar Industry of Pakistan. Secondary data of the non-financial companies which are listed on KSE is used for sugar industry over the last five years. Present study used different analytical tools like Reliability Analysis, Descriptive Statistics, Multiple Regression Analysis, Correlation and tests of significance to test the causal linkage in liquidity and profitability. Results of regression analysis showed that, hypothesis one is rejected because liquidity generates positive impact on ROA and found significant at 1% level. Hypothesis two of the current study is rejected because liquidity causes positive impact on ROE and found significant at 1% level. According to regression analysis, hypothesis three is also rejected because liquidity influences ROCE positively and found significant at 1% level. Results of correlation analysis discovered that liquidity of Sugar Mills is positively and significantly correlated with all measures of profitability i.e. ROA, ROE and ROCE. Findings of current research suggest managers to come out of the dilemma with respect to liquidity and profitability tradeoff. It is further concluded that managers can increase the firm's profitability and shareholder's value if they invest effectively and efficiently in liquid assets. Finally this study's results make it important for the reason that it is one of the fewer researches going in contrast to the existing knowledge base. Keywords: Liquidity, Profitability, Trade-off, Sugar Industry of Pakistan JEL Classification: G33